1994
DOI: 10.1073/pnas.91.26.12413
|View full text |Cite
|
Sign up to set email alerts
|

Two separate areas of the brain differentially guide the development of a song control nucleus in the zebra finch.

Abstract: A brain nucleus that is important for the generation of song in the adult male zebra finch (Poephila guttata), the robust nucleus of the archistriatum (RA), receives dual inputs from two other telencephalic song nuclei: the hyperstriatum ventrale pars caudale (HVc) and the lateral magnocellular nucleus of the anterior neostriatum (L-MAN). We lesioned each of these afferent inputs to the RA early in development, either by themselves or both at the same time in the same side of the brain, to determine what influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 19 publications
5
39
1
Order By: Relevance
“…This study shows that ARs and ERs within HVC are necessary for an increase in firing rates and soma area in RA, extending previous, purely morphometric studies of RA afferent input (Herrmann and Arnold, 1991;Akutagawa and Konishi, 1994;Burek et al, 1995;Brenowitz andLent, 2001, 2002). By infusing DHT and E 2 near HVC in SD birds, we demonstrated that coactivation of ARs and ERs in HVC is sufficient for an increase in firing rate and soma area in RA.…”
Section: A Model Of How T and Its Metabolites Induce Changes In Activsupporting
confidence: 87%
“…This study shows that ARs and ERs within HVC are necessary for an increase in firing rates and soma area in RA, extending previous, purely morphometric studies of RA afferent input (Herrmann and Arnold, 1991;Akutagawa and Konishi, 1994;Burek et al, 1995;Brenowitz andLent, 2001, 2002). By infusing DHT and E 2 near HVC in SD birds, we demonstrated that coactivation of ARs and ERs in HVC is sufficient for an increase in firing rate and soma area in RA.…”
Section: A Model Of How T and Its Metabolites Induce Changes In Activsupporting
confidence: 87%
“…The absence of topographic organization within the lMAN core 3 RA circuit in juvenile DF/WN birds may affect organization within other circuits as well, such as the projection between the higher vocal center (HVC) and RA that assumes increasing control of song production as vocal learning proceeds (Nottebohm et al, 1982;Akutagawa and Konishi, 1994). Individual RA neurons are contacted by axons from lMAN core as well as from HVC by 20 d in male zebra finches (Mooney and Rao, 1994;Foster and Bottjer, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…RA was intensely immunoreactive for TrkB, the receptor for NT-4/5, and it is possible that endogenous auto/paracrine release of NT-4/5 within RA could be regulated by presynaptic input from lMAN (antibodies to recognize NT-4/5 in avian brain are not presently available). With respect to the presence of multiple growth factors in RA, it is important to recognize that RA shows a complex assortment of developmental changes during song learning, including rapid overall growth that is attributable to a substantial increase in the size and spacing of neuronal somata and the delayed arrival of new axons from another cortical song region, HVC (Bottjer et al, 1985(Bottjer et al, , 1986Konishi and Akutagawa, 1985;Nordeen and Nordeen, 1988;Kirn and DeVoogd, 1989;Akutagawa and Konishi, 1994). Because neurotrophins have been shown recently to regulate the growth of somata, dendritic arbors, and axon terminals (Cabelli et al, 1995;Cohen-Cory andFraser, 1995, McAllister et al, 1995;Riddle et al, 1995), it seems likely that multiple anterograde, retrograde, and auto/paracrine signaling pathways could be involved in orchestrating the overall growth and development of RA.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical basis of redundant trophic signaling may lie in the fact that neuronal populations in the mammalian forebrain generally make and receive a large number of (often reciprocal) synaptic connections with several neuronal populations (Snider, 1994); glial and auto/ paracrine mechanisms of neurotrophin release may also contribute to redundant neurotrophic signaling (Acheson et al, 1995;Yan et al, 1995). By comparison, because the song-control system in the avian forebrain contains large populations of neurons that typically contact a limited number of afferent inputs and efferent targets in a serial, nonreciprocal manner (Bottjer et al, 1989;Johnson et al, 1995;Vates and Nottebohm, 1995), the loss of even one input or target removes a major source of trophic support and can result in extensive anterograde or retrograde neurodegeneration Bottjer, 1993, 1994;Akutagawa and Konishi, 1994). However, even among song-control regions, the requirement for anterograde or retrograde trophic support is transient and appears to wane over the course of juvenile development (e.g., deafferentation of RA ceases to induce neuron death by 40 d of age; Johnson and Bottjer, 1994;cf.…”
Section: Discussionmentioning
confidence: 99%